A comparative study between tramadol and fentanyl in spinal anesthesia in cesarean section - Salama, Abd AlHadi; Ibrahim, Taysir; Karam, Saleh (Latakia University Journal -Medical Sciences Series, 2018)
Study Objective: Studying the efficacy of adding tramadol to spinal anesthesics for postoperative analgesia. Setting: This study was carried out in the department of anesthesia and reanimation at Tishreen University Hospital, Lattakia, Syria during 2015-2016. Patients: The study included 75 patients classified ASA I and II, and were scheduled for elective cesarean section under spinal anesthesia. Interventions: Patients were randomly divided into 3 groups (25 in each group): Patients of group (A) received 12.5 mg bupivacaine 0.5% (3ml) + 25 μg fentanyl (½ml) Patients of group (B) received 12.5 mg bupivacaine 0.5% (3ml) + 25 mg tramadol (½ml) Patients of group (C) received 12.5 mg bupivacaine 0.5% (3ml) + normal saline (½ml) Pain relief duration of each group, side effects, Blood pressure, heart rate and O2 saturation, were recorded. Results: Analgesia duration was greatly prolonged in Tramadol group, and side effects were significantly lower than Fentanyl group. Conclusion: 25 mg of intrathecal tramadol with bupivacaine cause a prolonged analgesia duration with no significant side effects. دراسة مقارنة بين الترامادول والفنتانيل في التخدير الشوكي في العملية القيصرية هدف الدراسة: دراسة فعالية مشاركة الترامادول مع أدوية التخدير الشوكي في التسكين بعد العمل الجراحي. مكان الدراسة: أجريت هذه الدراسة في قسم التخدير والإنعاش في مشفى تشرين الجامعي - اللاذقية - سورية خلال عامي 2015 - 2016. عينة البحث: شملت الدراسة 75 مريضة من مراجعي مشفى تشرين لإجراء عملية قيصرية انتخابية تحت التخدير الشوكي ينتمون إلى الصنف I و II حسب تصنيف ASA . طريقة ومواد البحث: تم توزيع المرضى عشوائياً إلى 3 مجموعات (25 في كل مجموعة): عند مرضى المجموعة (A) تم حقن 12.5 ملغ بوبيفاكائين 0.5% (2.5 مل) + 25 مكغ فنتانيل (½مل) عند مرضى المجموعة (B) تم حقن 12.5 ملغ بوبيفاكائين 0.5% (2.5 مل) + 25 ملغ ترامادول (½مل) عند مرضى المجموعة (C) تم حقن 12.5 ملغ بوبيفاكائين 0.5% (2.5 مل) + نورمال سالين (½مل) تم تسجيل فترة التسكين الخاصة بكل مجموعة، الآثار الجانبية، ضغط الدم، معدل النبض والإشباع الأوكسجيني. نتائج الدراسة: فترة التسكين كانت أطول بشكل كبير لدى مرضى مجموعة الترامادول، والآثار الجانبية المسجلة كانت بنسبة أقل من مجموعة الفنتانيل. الخلاصة: الترامادول داخل القراب بجرعة 25 ملغ مع البوبيفاكائين يسبب إطالة مدة التسكين بدون إحداث تأثيرات جانبية مهمة.